2003
DOI: 10.1007/s00299-003-0636-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of haploid and doubled haploid plants of melon (Cucumis melo L.) for use in breeding for multiple virus resistance

Abstract: We have developed improved procedures for recovery of haploid and doubled haploid (DH) melon plants, using hybrids derived from crosses of lines with multiple virus resistance. Seeds formed after pollination with irradiated pollen were cultured in liquid medium for 10 days before excision of the embryos for further culture. This made it easier to identify the seeds containing parthenogenetic embryos, thereby reducing the effort required and increasing the percentage of plants recovered. The plants obtained (ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 18 publications
11
51
2
4
Order By: Relevance
“…Several protocols for melon have been described using different explants such as hypocotyls, cotyledons, leaves and roots (Moreno et al, 1985;Trulson and Shahin, 1986;Niedz et al, 1989;Bordas et al, 1991;Tabei et al, 1991;Souza, 1999;Souza, 2001;Lotfi et al, 2003). The results have shown that protocols using leaf explants were less efficient.…”
Section: Resultsmentioning
confidence: 76%
“…Several protocols for melon have been described using different explants such as hypocotyls, cotyledons, leaves and roots (Moreno et al, 1985;Trulson and Shahin, 1986;Niedz et al, 1989;Bordas et al, 1991;Tabei et al, 1991;Souza, 1999;Souza, 2001;Lotfi et al, 2003). The results have shown that protocols using leaf explants were less efficient.…”
Section: Resultsmentioning
confidence: 76%
“…Both in vitro androgenesis and gynogenesis have been induced in cucurbit crops for doubled haploid production (Metwally et al, 1998;Lotfi et al, 2003;Song et al, 2007;Gałązka and Niemirowicz-Szczytt, 2013). However, many reports show low frequency of gynogenesis and/or regeneration rates that limit their success in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…DHs can facilitate the selection of desired (e.g., disease-resistance) genotypes for breeding. Lotfi et al (2003) used a hybrid melon which showed resistance to various viruses as a donor for the production of DH melons. DH cucumber is produced by culturing the ovaries at one day before an thesis to induce new plants through cytogenesis.…”
Section: Discussionmentioning
confidence: 99%